ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA BERKEMAMPUAN AWAL TINGGI DAN RENDAH DENGAN MENGGUNAKAN PENDEKATAN OPEN-ENDED DI SMA NEGERI KABUPATEN PADANG LAWAS UTARA - siregar, yulia pratiwi (Universitas Aufa Royhan, 2021)
Education and these skills can be obtained from the learning process in schools including students' mathematical problem solving abilities. This study aims to look at the description of mathematical problem solving abilities in students with high and low initial abilities, especially in Class X SMA Negeri 1 Padang Bolak. The population in this study were all students of Class X SMA Negeri 1 Padang Bolak which consisted of 5 classes totaling 150 people. The sampling technique was carried out by random sampling technique so that the sample in the study was as many as two classes, namely X2 and X3 classes. The research instrument in this study was to use an essay test in the form of open questions (Open-Ended). Based on the first hypothesis test, it was concluded that the value of Sig. < 0.05 or 0.0005 < 0.05 then H0 is rejected and H1 is accepted. Thus, it can be concluded that the problem solving abilities of students with high initial abilities who are taught using an open-ended approach are better than students with high initial abilities who are taught using a conventional approach. Furthermore, based on the second hypothesis test, it can be seen that the problem-solving ability has a Sig value. of 0.0195. It means the value of Sig. < 0.05 or 0.0195 < 0.05 means that H0 is rejected and H1 is accepted. Thus, it can be said that the problem solving abilities of students with low initial abilities who are taught with an open-ended approach are better than students with low initial abilities who are taught using conventional learning.